Endoscopy- and Monitored Anesthesia Care-Assisted High-Resolution Impedance Manometry Improves Clinical Management - Kaci E. Christian; John D. Morris; Guofeng Xie (Case Reports in Gastrointestinal Medicine)
Background. High-resolution impedance manometry (HRiM) is the test of choice to diagnose esophageal motility disorders and is particularly useful for identifying achalasia subtypes, which often guide therapy. HRiM is typically performed without sedation in the office setting. However, a substantial number of patients fail this approach. We report our single-center experience on endoscopy-assisted HRiM under monitored anesthesia care (MAC) in adults to demonstrate the feasibility and effectiveness of this approach. Methods. Patients who had failed prior HRiM attempts received propofol under MAC. Patients then underwent an upper endoscopy, followed immediately by passage of a Diversateck HRiM motility catheter through the nares and under direct visualization into the stomach, often using the tip of the endoscope to guide the catheter. We then awakened the patients and asked them to perform 10 saline swallows. Results. We successfully completed HRiM studies in 14 consecutive patients. Six patients had achalasia; two had esophagogastric junction outflow obstruction; two had absent contractility; one had distal esophageal spasm; one had ineffective esophageal motility; and one had a normal study. The majority of these patients were treated successfully with targeted interventions, including per oral endoscopic myotomy, gastrostomy, botox injection, medical therapy, and dietary modifications.